Strategi Guru Sejarah dalam Merancang Pembelajaran yang Bermakna di Abad 21 - Susidah Ernawati; Sabitah Salwa; Eggi Martiansyah; Sani Safitri; Rani Oktapiani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
History learning plays a crucial role in fostering historical awareness, fostering national character, and enhancing students' critical thinking skills. However, the history learning process in schools is often oriented toward memorization and the presentation of facts, rendering it less meaningful for students. The 21st century demands that teachers be innovative in designing active, collaborative, and real-life learning. This article aims to describe history teachers' strategies for designing meaningful learning in accordance with the demands of 21st-century competencies. The method used is a literature study, examining various theories, research findings, and the latest educational policies. The study results indicate that strategies teachers can implement include analyzing student characteristics, implementing innovative learning models such as Project-Based Learning and Inquiry Learning, utilizing digital technologies such as Augmented Reality and virtual museum tours, and implementing authentic project-based assessments. Through these strategies, teachers can create engaging, contextual, and meaningful history learning experiences, while simultaneously fostering students' historical thinking skills and national values ​​in the digital era.